Levels of trust in information sources as a predictor of protective health behaviors during COVID-19 pandemic: A UAE cross-sectional study - Figueiras, Maria Joao (2021)
Health information sources and the level of trust in a particular source may influence the subsequent adoption of advocated health behaviors. Information source preference and levels of trust are also likely to be influenced by sociodemographic (culture, age, gender) variables. Understanding these source-trust-behavior relationships across various national and cultural contexts is integral to improved health messaging. The present study identified the sources most frequently consulted to obtain information about COVID-19 during the pandemic’s early stages in the United Arab Emirates (UAE). The study quantified levels of trust across an array of information sources, factoring in sociodemographic variables. Finally, the study explored the relationship between sociodemographic variables, levels of trust in information sources, and the adoption of COVID-19 related protective behaviors. Participants (n = 1585) were recruited during the first 2 weeks of April 2020 via announcements in the UAE media and through email networks. All participants completed a web-based survey presented in English or Arabic, as preferred. The most frequently consulted information sources were websites (health information websites), social media, government communications, and family and friends. The sources rated most trustworthy were: personal physicians, health care professionals, and government communications. There were differences in the use of sources and levels of trust according to age, gender, and education. The levels of trust in sources of information were associated with the adoption of protective behaviors, significantly so for citizens of the UAE. These findings may help inform the improvement of pandemic–related health messaging in multicultural contexts.